Autistic Intelligence: Interaction, Individuality, and the Challenges of Diagnosis - Jessica Coombs (Studies in Applied Linguistics & TESOL, 2023)
Autistic Intelligence: Interaction, Individuality, and the Challenges of Diagnosis by Maynard and Turowetz (2022) addresses the importance of exploring language used in interactions during the diagnostic process of autism spectrum disorder. The authors analyze interaction in order to clarify the ambiguity in understanding autism that exists across several fields of study. Drawing on their sociological backgrounds, the authors use an ethnomethodological conversation analytic approach to show that interaction has been overlooked in the autism diagnostic process. This research makes an important contribution to existing conversation analytic and psychological literature by reframing autism spectrum disorder as a difference rather than a deficit.